Shari'ah alternative approaches on Islamic swaps transactions : towards innovative instruments in Shariah compliant derivatives - Muhammad Adnan Bin Hasan (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2010)
Islamic swaps are one of the largest and fastest growing Islamic derivative markets. This financial instrument is one of the most important classes of Islamic derivative instruments which are practiced in the Islamic capital market in Malaysia. This financial instrument is very useful, not only for risk management, but also for reducing the cost of finance, for smoothing seasonal cash flows, for arbitraging the yield curve, for creating synthetic instruments, for entering new markets and also for exploiting economies of scale. The usage of Islamic swaps are under Shari'ah alternative approach, based on taflawwut (Hedging) tools, which are competitively priced to provide Islamic hedging solution to customers and clients who would like to look in their future movements in profit rates, currency rates, and also rental rates. The Islamic swaps applied are based on the concept ofwa'ad (unilateral binding promise) contract, commodity murtibaJ:rah, commodity mustiwamah, tawarruq and also Muqaseah, which is allowed under Islamic law. It is also classified as compliant with applicable Shari'ah rules and principles, as long as it is free from prohibited elements in Islamic finance. This study emphasizes the impmiance of Shari' ah compliance in Islamic Derivatives transactions, especially in Islamic swaps instrument, which is provided to reduce the potential Shari'ah 'arbitrage', as well as to make it easier for Islamic bankers and investors to understand the existing Islamic financial market. Finally, the study emphasizes the importance to make it clear that Islamic swaps transaction should not be utilized for speculation purposes. Therefore, the researcher strongly recommends introducing a genuine hedging mechanism for risk management to plan better with ideal and superlative.